2005
DOI: 10.1080/10915810590953437
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chlorine Dioxide as a Gas and in Solution in the Inactivation of Two Trichothecene Mycotoxins

Abstract: The efficacy of chlorine dioxide (ClO2) in detoxifying two potential bioterrorism agents, the trichothecene mycotoxins verrucarin A and roridin A, was evaluated. In the first experiment, verrucarin A (1, 5, or 10 microg) and roridin A (5 or 10 microg) were each inoculated onto square-inch sections of glass, paper, and cloth and exposed to 1000 ppm of ClO2 for either 24 or 72 h at room temperature. In the second experiment, verrucarin A and roridin A (1 or 2 ppm in water) were treated with 200, 500, or 1000 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Furthermore, the gaseous ClO 2 exposure did not decrease the activity of two trichothecene mycotoxins (roridin A and verrucarin A) or trichothecene mycotoxins from S. chartarum spores. 22,33 These results are consistent with the data from our field study because no change was observed in the semiquantitative microscopic evaluation of tape samples to assess surface contamination, but a clear decrease was seen in the culturable and total count of airborne spores. Furthermore, an increasing trend was observed for endotoxin and (133)-␤-D-glucan both in the laboratory and field study supporting the results of Wilson et al on the inefficiency of ClO 2 treatment in reducing the concentrations of fungal components.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the gaseous ClO 2 exposure did not decrease the activity of two trichothecene mycotoxins (roridin A and verrucarin A) or trichothecene mycotoxins from S. chartarum spores. 22,33 These results are consistent with the data from our field study because no change was observed in the semiquantitative microscopic evaluation of tape samples to assess surface contamination, but a clear decrease was seen in the culturable and total count of airborne spores. Furthermore, an increasing trend was observed for endotoxin and (133)-␤-D-glucan both in the laboratory and field study supporting the results of Wilson et al on the inefficiency of ClO 2 treatment in reducing the concentrations of fungal components.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, an increasing trend was observed for endotoxin and (133)-␤-D-glucan both in the laboratory and field study supporting the results of Wilson et al on the inefficiency of ClO 2 treatment in reducing the concentrations of fungal components. 22,33 Rendering microorganism nonculturable will prevent microbial growth and further production of harmful agents, such as endotoxin, (133)-␤-D-glucan, mycotoxins, and allergens. However, the destruction of bacterial cells, fungal spores, and hyphae during the treatment will not remove these components.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these efforts, contamination of grain with DON continues to pose a threat to grain production. The chemical detoxification of DON in solution and on/in contaminated grains by ozone (Young et al 2006), ammonia, chlorine, hydrogen peroxide, sodium bisulfite (Young et al 1986), sodium carbonate (Abramson et al 2005), and chlorine dioxide (Wilson et al 2005) has been demonstrated, but its application on a large scale has been hampered by costs, safety concerns, and the negative impact on grain quality. The most promising technique for chemical detoxification of DON is reaction with sodium metabisulfite (Young et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical degradation of DON has been achieved by ammonia, calcium hydroxide, chlorine, hydrochloric acid, ozone, sodium bisulfite, and sodium hydroxide. [133][134][135][136] However, the large-scale application of these methods are hampered by costs, safety concerns and the negative impact on grain quality. 137 Biological detoxification, defined as the enzymatic degradation of mycotoxins or modification of their structure that leads to less toxic products, offers an alternative method to reduce the mycotoxin content in food and feed products.…”
Section: Post-harvest Controlmentioning
confidence: 99%